2013
DOI: 10.1016/j.rmed.2013.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Resting and ADL-induced dynamic hyperinflation explain physical inactivity in COPD better than FEV1

Abstract: The presence of resting hyperinflation and occurrence of dynamic hyperinflation during ADL contribute to reduced physical activity levels in patients with COPD, independently of the degree of airflow limitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 33 publications
1
25
1
1
Order By: Relevance
“…The increment of dynamic hyperinflation and decrease in inspiratory reserve volume (IRV = TLC (total lung capacity)-EELV) increase dyspnoea and reduce exercise tolerance in COPD patients (15). Physical activity in patients with COPD decreases with dynamic hyperinflation during exercise.…”
Section: Critical Inspiratory Reserve Volume and Exercise Tolerancementioning
confidence: 99%
See 2 more Smart Citations
“…The increment of dynamic hyperinflation and decrease in inspiratory reserve volume (IRV = TLC (total lung capacity)-EELV) increase dyspnoea and reduce exercise tolerance in COPD patients (15). Physical activity in patients with COPD decreases with dynamic hyperinflation during exercise.…”
Section: Critical Inspiratory Reserve Volume and Exercise Tolerancementioning
confidence: 99%
“…Physical activity in patients with COPD decreases with dynamic hyperinflation during exercise. Dynamic hyperinflation worsens dyspnoea on exercise and quality of life (15). As dynamic hyperinflation increases, IRV can fall below a critical level in daily life (7,15).…”
Section: Critical Inspiratory Reserve Volume and Exercise Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Even one third of the patients with mild COPD in our study showed DH during ADL. In a recent study, also including patients with mild COPD, we found that a lower level of physical activity in patients with COPD is related to hyperinflation during ADL, independently of the severity of airflow limitation [23]. Testing patient performance in ADL, however, is not practical in most clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 56 COPD evaluated the relation between lung function indices (including a measure of DH during an activity of daily living (ADL) task performed at the patient's home) and average daily physical activity. The authors found that both resting IC/TLC ratio and ADL-induced change in IC were the two main determinants of daily activity levels, with no significant contribution of FEV1 [68].…”
Section: Characteristics Of the Eh Phenotype: Emphysemamentioning
confidence: 97%